The potential for dairy development in West Africa - Smith, Jimmy W.; Agyemang, K. (South African Society of Animal Science, 1996)
Rapid population growth (from 498 million in 1990 to 1.2 billion by 2025) and urbanization (from 2.7:1 to 5.1 rural to urban) in sub-Saharan Africa will profoundly influence the demand for food including milk and other dairy products. Since West Africa accounts for over 42 percent of SSA population, these trends are likely to be accentuated there. Demand (2.2 MT in 1989) for milk alone in West Africa was much greater than indigenous supply (1.4 MT in 1989). Thus a rapid production response, mostly through increases in productivity, is required.This paper attempts to explore the potential of the dairy sector in West Africa to (a) meet the future dairy food needs (b) earn or save foreign exchange and (c) generate farm income and employment.